VISUALISASI DATA AKREDITASI PROGRAM STUDI BERBASIS WEB MENGGUNAKAN EXTREME PROGRAMMING - Muh. Fahmi Rustan; Hasriani; Nuralamsah Zulkarnaim (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
The accreditation status of a study program is determined by a lot of data that can support the assessment criteria. The availability of data certainly supports the amount of information that can be obtained so that it will be easier if the data is collected in one accreditation system. Yet it is not easy to understand the information from unstructured data. Thus, a brief and interesting presentation of information on the accreditation system is needed. This can be realized through data visualization where information can be obtained by exploring, understanding, and communicating data. Data visualization is also a tool for conducting data analysis. Moreover, This research aims to develop a study program accreditation system that focuses on educational criteria and is equipped with data visualization that can assist the data analysis process so that users or policymakers are able to make the right decisions. By utilizing the Extreme Programming (XP) method, this research produces a study program accreditation system that is equipped with data visualization which enables to presentation of effective and attractive data displays. The results of this study will make the users be easier to make decisions regarding efforts to achieve study program accreditation.